Report and resolution at the 16th International Symposium "Minor invasive and instrumental spinal surgery" conducted on the basis of the Sytenko Institute of Spine and Joint Pathology National Academy of Medical Sciences of Ukraine, Kharkiv under the ausp - Radchenko, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Report and resolution at the 16th International Symposium "Minor invasive and instrumental spinal surgery"